Mainstreaming the Third Sector Economics by Adopting the Principles of Islamic Entrepreneurship: For Development with Equity and Social Justice - Molla, Rafiqul Islam (IIUC Studies, 2015)
The private and public sector economics found their own strong places to play roles in the mainstream economy. At the end, however, these two systems the private, popularly called the first sector economy, and the public, called the second sector economy - both individually and jointly have been found seriously inadequate and incapable to ensuring wellbeing of human societies nationally and globally. Responding to such a situation a number of non-conventional approaches like cooperatives and social enterprises, waqaf, foundations, and other non-profit institutions, etc., together called third sector economy, were moved and promoted to ensure social justice and wellbeing of mankind. Initially it emerged as a make-up and defensive strategy of the market-state model to meet the minimum of unmet requirements in the sectors where the market and state have grossly failed. It, thus, played only a subordinate role. As a result, it could not help much to solve the problem of economic inequity, concentration of wealth, and social divides. However it is strongly felt that a broadly based third sector economic model with both not for-profit business like enterprises and for-profit businesses blended with social justice is necessary to play its role as a mainstream model not only for poverty alleviation but also for economic growth to bridge the economic and social divides. Mainstreaming the third sector is the urgent call of the day. Islamic entrepreneurship, which is basically a communitycentric mode of business initiative, is an antidote to the problem of intolerable economic and social dualism in the economies. It is a natural strategy against all forms of capitalist exploitations, like in the past through European colonialism and now through American led terrorism, to control resources. Accordingly it is the natural model for solving the problems of economic inequity, concentration of wealth, and social divides. Therefore, this study finds the Islamic mode of entrepreneurship as most suitable and effective for widening and mainstreaming the third sector economics, more particularly in the developing countries. Johor Corporation (JCorp) in Malaysia and Sheba Polly in Bangladesh are examples of two types of Islamic style third sector enterprises one is staunchly business like initiative and the other is cost based charity initiative for social benefit. For the development and promotion of the community-centric third sector economics model, the paper recommends for urgently establishing a research and development centre on third sector economics preferably under an Islamic Research and Development Institute in any reputed university. IIUC Studies Vol.9 December 2012: 39-58